2012
DOI: 10.1186/1471-2164-13-s7-s18
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of microRNAs in breast cancer

Abstract: Background MicroRNAs (miRNAs) are short noncoding RNAs (approximately 22 nucleotides in length) that play important roles in breast cancer progression by downregulating gene expression. The detailed mechanisms and biological functions of miRNA molecules in breast carcinogenesis have yet to be fully elucidated. This study used bioinformatics and experimental approaches to conduct detailed analysis of the dysregulated miRNAs, arm selection preferences, 3' end modifications, and position shifts in iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 55 publications
4
35
0
Order By: Relevance
“…However, we obtained interesting data showing significantly different arm selection preferences of miR-324 in human cancer tissues and the corresponding adjacent normal tissues ( Figure 1C). This finding is in concordance with our previous findings that arm selection preferences of some miRNAs varied in different tissues, developmental stages, species, and cancer types (7)(8)(9)(10)23).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, we obtained interesting data showing significantly different arm selection preferences of miR-324 in human cancer tissues and the corresponding adjacent normal tissues ( Figure 1C). This finding is in concordance with our previous findings that arm selection preferences of some miRNAs varied in different tissues, developmental stages, species, and cancer types (7)(8)(9)(10)23).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, miR-324-5p has been shown to suppress glioma and HCC cell growth (19,20). We previously reported that the selection preference of miR-324 for 5p and 3p arms significantly varied in breast cancer compared to that in adjacent normal tissues analyzed using next-generation sequencing data from the Sequence Read Archive database (8). However, the related biological functions of miR-324-5p and -3p require clarification in human cancer.…”
mentioning
confidence: 99%
“…In rats, miR-511-3p is relatively abundant in isolated LSECs (Figure 2A) and the liver 9 compared with miR-511-5p, and is also abundant in humans, at least in breast cancer cells. 38 Thus, further studies on disease or injury specificity of plasma miR-511-3p are needed. ajp.amjpathol.org -The American Journal of Pathology In summary, we provided miRNA expression profiles in the isolated hepatocytes and LSECs from rats and identified LSEC-specific miRNAs by considering organ specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Although, miR-21-3p and -5p are generated from the same precursor (pre-miR-21), the role and biological function of the passenger strand, miR-21-3p, in OSCC remains unclear. Moreover, studies have indicated that the expression of miR#-5p and -3p arms is frequently coexpressed and coordinately regulated in human cancers (22)(23)(24). Therefore, the expression preference of the -5p and -3p arms of most miRNAs is consistent in human cancers; only a few of the miR-#-5p and -3p arms can be preferentially selected during cancer progression, which suggests that they might have a distinct biological function in human cancers (23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%